A Model for Understanding Positive Intergroup Relations Using the In‐Group‐Favoring Norm. (September 2016) - Montoya, R. Matthew; Pinter, Brad
Abstract : We present a model of intergroup relations focused on the role of the in‐group‐favoring norm as capable of facilitating positive intergroup relations. We begin by defining the in‐group‐favoring norm and describing how it affects self‐evaluations and evaluations of out‐group members. We then outline how positive intergroup relations may result via the implementation of specific techniques fundamental to the in‐group‐favoring norm, including emphasizing the value of interactions with the out‐group, establishing cooperative intergroup norms, and establishing superordinate goals. In so doing, we discuss how classic moderators of intergroup relations, including leadership, guilt, and in‐group norms are facilitators of positive intergroup relations once in‐group interests are considered.